Analisis Swot dalam Strategi Penghimpunan dan Pendayagunaan Zakat Di Inisiatif Zakat Indonesia - Musdalifah musdalifah; Rahman Ambo Masse; Trisno wardy Putra (Publikasi Indonesia, 2022)
This study aims to determine the extent of swot analysis in the strategy of collecting and utilizing zakat in the Indonesian zakat initiative (IZI) representatives of South Sulawesi, whether it makes a difference to the lives of mustahiq who are empowered and in accordance with the basic principles of Islamic law. This type of research uses qualitative methods with a descriptive approach, the data sources used are primary data and secondary data, then the data collection techniques used are observation, interviews, documentation, how to analyze the data in this study using the Milens and Huberman method, which stages are data collection, descriptive data, data reduction, data presentation, data verification, and conclusion drawing, then test the validity of the data in this study using credibility, transferability, dependability, and confirmability tests. The results of this study indicate that there is a swot analysis in the strategy of collecting and utilizing zakat carried out by the national amil zakat institution IZI South Sulawesi, which provides positive changes for the economic improvement of mustahiq who are empowered, the utilization of this zakat for mustahiq done by IZI South Sulawesi in accordance with the principles of sharia, and the collection carried out by IZI so that muzakki knows more about the obligation to give zakat and mustahiqs are given business capital by IZI not out of eight asnaf, in the provision of zakat funds mustahiqs are not charged to return compensation funds because it has become the absolute right of mustahiqs.